ANALISIS PERTIMBANGAN HUKUM HAKIM TENTANG CERAI GUGAT DI PENGADILAN AGAMA PUTUSIBAU DALAM PUTUSAN NOMOR 19/PDT.G/2022/PA.PTS - NIM. A1012191089, MUHAMMAD BUSTAMIN (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract In the case of divorce, one of the conditions that must be met to carry out a divorce in the Religious Courts is that apart from strong reasons, the marriage certificate must also be included when filing for divorce to the Religious Courts as proof of marriage. Problems arise when a marriage is carried out legally according to religious law but is registered and then wants to divorce officially in the Religious Courts with the aim that after a divorce the rights of every legal action carried out in a marriage are protected by law, for example regarding shared assets or regarding custody and responsibility towards children.For example, the case in Decision Number 19/Pdt.G/2022/PA.Pts in the Putussibau Religious Court regarding Divorce filed by a Wife against Husband. according to religious law without being registered with the local Marriage Registrar (KUA), regarding this matter it is interesting to study how the legal considerations of the judges of the Putussibau Religious Court Number 19/Pdt.G/2022/PA.Pts Regarding the wife's divorce against her husband?This research was conducted using normative research methods with a statutory regulation approach combined with a case approach and a legal concept analysis approach. This research activity includes analyzing certain articles in laws and regulations which are then analyzed and interpreted with legal concepts originating from legal theory, legal principles and Islamic ushul fiqh principles which are associated with certain cases by referring to Court Decisions.Based on the results of research and discussion of,